Answer this for me to mark you as brainliest
Attachments:
![](https://hi-static.z-dn.net/files/d6c/af46ecc798f87c5d5ff4b4608b14bd58.jpg)
Answers
Answered by
0
Answer:
2
Step-by-step explanation:
(4 *3)÷6
12*1/6
=2
please tell is it helpful
Answered by
0
(4^-1*3^-1)/6^-1
=(1/4*1/3)/1/6
=(1/12)*6
=1/2
=(1/4*1/3)/1/6
=(1/12)*6
=1/2
Similar questions
Science,
5 months ago
Hindi,
5 months ago
Social Sciences,
5 months ago
Chemistry,
10 months ago
Economy,
1 year ago
Environmental Sciences,
1 year ago